Neurological Manifestations and Outcomes in a Retrospective Cohort of Mexican Inpatients with SARS-CoV-2 Pneumonia: Design of a Risk Profile - Silvia García (MDPI AG, 2021)
We analyzed the neurological manifestations in Mexican patients hospitalized with pneumonia due to COVID-19 and investigated the association between demographic, clinical, and biochemical variables and outcomes, including death. A retrospective, analytical study was conducted using the electronic records of patients hospitalized between 1 April 2020 and 30 September 2020. Records of 1040 patients were analyzed: 31.25% died and 79.42% had neurological symptoms, including headache (80.62%), anosmia (32.20%), ageusia (31.96%), myopathy (28.08%), disorientation (14.89%), encephalopathy (12.22%), neuropathy (5.4%), stroke (1.3%), seizures (1.3%), cerebral hemorrhage (1.08%), encephalitis (0.84%), central venous thrombosis (0.36%), and subarachnoid hemorrhage (0.24%). Patients also had comorbidities, such as hypertension (42.30%), diabetes mellitus (38.74%), obesity (61.34%), chronic obstructive pulmonary disease (3.17%), and asthma (2.01%). Factors associated with neurological symptoms were dyspnea, chronic obstructive pulmonary disease, advanced respiratory support, prolonged hospitalization, and worsening fibrinogen levels. Factors associated with death were older age, advanced respiratory support, amine management, chronic obstructive pulmonary disease, intensive care unit management, dyspnea, disorientation, encephalopathy, hypertension, neuropathy, diabetes, male sex, three or more neurological symptoms, and obesity grade 3. In this study we designed a profile to help predict patients at higher risk of developing neurological complications and death following COVID-19 infection.